Dualization of corporate control: lifetimers, external appointees, and CEO succession in Japan. - Jung, Jiwook; Mun, Eunmi; Ono, Hiroshi (Social Forces, 2026)
We investigate mechanisms of institutional stability under profound environmental change, using corporate control in Japan as a critical case. Building on the concept of dualization in the comparative institutions literature, we theorize how dualized power relations at the top of the firm sustain insider control. Using data on executive board members of all non-financial firms listed on the Tokyo Stock Exchange from 1993 to 2016, we show that "lifetimers"—employees who spend their entire careers with a single company—continue to enjoy substantial advantages in CEO succession. They maintain their dominance by promoting fellow lifetimers and constraining the prospects of other candidates. At the same time, "external appointees"—organizational outsiders who join the firm directly as executive board members—also benefit from their institutional ties and boundary-spanning roles. Yet, unlike lifetimers, their relative advantages are fragile, as they lack durable intra-firm power bases and are more exposed to shifting external conditions and internal politics. Our findings suggest that resistance by organizational insiders, combined with the selective co-optation of outsiders, can help preserve institutional arrangements in a changing environment.